Structural Control on Megathrust Rupture and Slip Behavior: Insights From the 2016 Mw 7.8 Pedernales Ecuador Earthquake. Issue 2 (1st March 2020) - Soto‐Cordero, Lillian; Meltzer, Anne; Bergman, Eric; Hoskins, Mariah; Stachnik, Joshua C.; Agurto‐Detzel, Hans; Alvarado, Alexandra; Beck, Susan; Charvis, Philippe; Font, Yvonne; Hayes, Gavin P.; Hernandez, Stephen; et al.
Abstract: The heterogeneous seafloor topography of the Nazca Plate as it enters the Ecuador subduction zone provides an opportunity to document the influence of seafloor roughness on slip behavior and megathrust rupture. The 2016 Mw 7.8 Pedernales Ecuador earthquake was followed by a rich and active postseismic sequence. An internationally coordinated rapid response effort installed a temporary seismic network to densify coastal stations of the permanent Ecuadorian national seismic network. A combination of 82 onshore short and intermediate period and broadband seismic stations and six ocean bottom seismometers recorded the postseismic Pedernales sequence for over a year after the mainshock. A robust earthquake catalog combined with calibrated relocations for a subset of magnitude ≥4 earthquakes shows pronounced spatial and temporal clustering. A range of slip behavior accommodates postseismic deformation including earthquakes, slow slip events, and earthquake swarms. Models of plate coupling and the consistency of earthquake clustering and slip behavior through multiple seismic cycles reveal a segmented subduction zone primarily controlled by subducted seafloor topography, accreted terranes, and inherited structure. The 2016 Pedernales mainshock triggered moderate to strong earthquakes (5 ≤ M ≤ 7) and earthquake swarms north of the mainshock rupture close to the epicenter of the 1906 Mw 8.8 earthquake and in the segment of the subduction zone that ruptured in 1958 in a Mw 7.7 earthquake. Key Points: A dense temporary seismic network provides a detailed view of the evolution of a megathrust rupture postseismic sequence The postseismic sequence is characterized by clusters of seismicity containing earthquake swarms and moderate to large aftershocks Seafloor topography and upper plate structure segment the subduction zone and control slip behavior across the seismic cycle